ISSUES OF PHYSICAL DEVELOPMENT OF YOUTH TASHKENT INSTITUTE OF FINANCE (Intent Research Scientific Journal, 2023)
Popularization of sports among young people, physical education and forms of wellness activities, physical development and wellness of young people processes were studied.